1993
DOI: 10.3354/meps093039
|View full text |Cite
|
Sign up to set email alerts
|

Viral mortality of the marine alga Emiliania huxleyi (Haptophyceae) and termination of algal blooms

Abstract: The possible roles of viruses in phytoplankton dynamics were investigated in seawater mesocosms with natural assemblages of phytoplankton growing under various nutrient regimes. Blooms of the marine coccolithophorid Emiliania huxleyi (Lohmann) Hay & Mohler were in some cases succeeded by an increase in the abundance of a morphologically homogeneous population of viruses. The viruses had an hexagonal outline and were about 180 nm in diameter. Similar viruses were found both intracellularly and associated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
465
4
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 493 publications
(483 citation statements)
references
References 19 publications
13
465
4
1
Order By: Relevance
“…It is suggested that high concentrations of phytoplankton might result in more planktonic viruses, and the significant correlation has been suggested by some previous studies (Boehme et al, 1993;Maranger & Bird, 1995;Weinbauer et al, 1995). In addition, phytoplankton had larger burst sizes than bacterioplankton, ranging from 92 to 500 (Bratbak et al, 1993;Suttle & Chan, 1994). In a previous study, we have found that there are large numbers of virus particles existing in algae tubule (Liu et al, 2005).…”
Section: Discussionmentioning
confidence: 49%
“…It is suggested that high concentrations of phytoplankton might result in more planktonic viruses, and the significant correlation has been suggested by some previous studies (Boehme et al, 1993;Maranger & Bird, 1995;Weinbauer et al, 1995). In addition, phytoplankton had larger burst sizes than bacterioplankton, ranging from 92 to 500 (Bratbak et al, 1993;Suttle & Chan, 1994). In a previous study, we have found that there are large numbers of virus particles existing in algae tubule (Liu et al, 2005).…”
Section: Discussionmentioning
confidence: 49%
“…Although such conclusions from similar data sets are not new (Bratbak et al, 1993Brussaard et al, 1996;Castberg et al, 2001), there have been no reports of E. huxleyi-speci¢c viruses being isolated and maintained in culture from E. huxleyi blooms. Bratbak et al (1996) reported the initial isolation of a virus by plaque assay, however they were unable to propagate it further for characterization.…”
Section: Discussionmentioning
confidence: 92%
“…This further supports the prediction made by Wilson et al (in press) who discussed that viruses would play a much more important role towards the end of a bloom when virus concentrations would reach a threshold level required to cause termination of that bloom. Indeed, numerous mesocosm studies have been conducted where high concentrations of LVLPs have been observed following the demise of the E. huxleyi population (Bratbak et al, 1993;Castberg et al, 2001). It is di¤cult to measure such termination at sea since it is not often logistically possible to be on a ship throughout the progression of a bloom.…”
Section: Transect Datamentioning
confidence: 99%
“…Several studies have investigated the role of viruses in controlling the bloom development of E. huxleyi (Bratbak et al, 1993, Brussaard et al, 1996, Castberg et al, 2001, Jaquet et al, 2002, Wilson et al, 1998, 2002a, 2002b. It became evident from these investigations that viruses are intrinsically linked to the decline of E. huxleyi blooms.…”
Section: Introductionmentioning
confidence: 99%